Validity of Pont’s analysis in a sample of Bangladeshi orthodontics patients - Haque Sajib, Najmul; Khursheed Alam, Mohammad (Journal of Oral Research, 2019)
To assess the applicability of Pont’s index for arch width prediction among the Bangladeshi population. Materials and Methods: Models of 37 male and 63 female subjects ranging in age between 16 to 25 years were sandomly selected out of all patients attending the Orthodontic clinic of Bangabandhu Sheikh Mujib Medical University (BSMMU). Teeth size and arch size were measured to determine the Pont’s value. Results: The reported value of Pont’s ratio is 0.87±0.08 (premolar) and 0.67±0.05 (molar). The mean value of Pont’s ratio in the present study is 0.88±0.07 and 0.67±0.05 for females, and 0.89±0.09 and 0.66±0.05 for males. The reported mean index value of Pont is 0.80 and 0.64 with the differences 0.03 and 0.01 whereas, in this study, index value were 0.87 and 0.67, and the differences are 0.07 and 0.03 respectively which are statistically significant compared to the reported values. Conclusion: Based on the results of the current study, Pont’s index is not applicable in the Bangladeshi population.